A Bibliometric Analysis of Talent Acquisition in Human Resource Management - Loso Judijanto; Rival Pahrijal; Rani Eka Arini (West Science Social and Humanities Studies, 2026)
Talent acquisition has become a strategic pillar of human resource management (HRM) as organizations compete for scarce skills in an increasingly digitalized labor market. This study conducts a bibliometric analysis to investigate the intellectual structure, thematic evolution, influential publications, and collaboration patterns of talent acquisition research within the human resource management literature. The data were collected from the Scopus database using the keywords "talent acquisition" and "human resource management" and analyzed using VOSviewer to conduct keyword co-occurrence analysis, overlay and density visualization, citation analysis, co-authorship analysis, institutional collaboration mapping, and country collaboration analysis. The results show that human resource management, talent management, talent acquisition, and recruitment constitute core themes linked with organizational decision-making, HR analytics, predictive analytics, artificial intelligence, and machine learning. Based on citation analysis, key contributions such as artificial-intelligence adoption for talent acquisition, crisis-responsive HRM strategy, and HRM-driven knowledge management capacity significantly influence the field. The collaboration analysis demonstrates that India serves as the dominant contributor and central hub of an international research network extending to the United Kingdom, the United States, China, and several European and Asian countries, while co-authorship and institutional mapping reveal small, loosely connected research communities bridged by a limited number of prolific scholars and universities. Furthermore, thematic evolution indicates a transition from traditional recruitment and workforce-planning perspectives toward artificial-intelligence-enabled, data-driven, and predictive talent-acquisition practices. This study contributes by providing a comprehensive mapping of talent acquisition research development and identifying critical research gaps for future scholarship, particularly regarding cross-institutional collaboration and the integration of emerging technologies with human-centered talent strategy.